Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah pada Usaha Mikro Kecil dan Menengah - Maryana, Gina (COMPETITIVE, 2023)
This research was conducted to determine the application of Accounting Standards Finance for Micro, Small and Medium Entities in Micro, Small and Medium Enterprises at the MSME Red Brick Factory in Cicantayan District. The study uses a qualitative method by using the method descriptive. The autor uses data collection techniques by means of observation fieldwork, interviews, and documentation. The autor performs data analysis techniques by describing the result obtained from field observations, interviews, and documentation. The results of this study indicate that the MSME of The Red Brick Factory in Cicantayan District has not recorded financial statements in accordance with SAK EMKM. Factors that affect the non-implementation of recording financial statements in accordance with SAK EMKM, namely: external factors, is including lack of understanding and discipline of MSME actors in recording financial statements in accordance with SAK EMKM. External factors, including the absence of supervision from stakholders interests (stakeholders) regarding the importance of recording financial statements in accordance with SAK EMKM Keywords: SAK EMKM, Recording of Financial Statements, MSME.